Biomarkers and clinical outcomes of hospitalized patients with COVID-19 - Silva, Doralice Limeira da; Moura, Maria Edileuza Soares (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: This study aims to analyze laboratory biomarkers in patients infected with SARS-CoV-2 in public hospitals in Maranhão and compare the results between those who were discharged and those who did not survive. Outlining: This cross-sectional study evaluated a sample of 192 medical records of patients admitted between July and December 2020. The study assessed variables such as sex, age group, race, comorbidities, length of hospital stay, symptoms, medication classes, and clinical biomarkers related to cardiac, hepatic, renal, and coagulation functions. The data were analyzed using SPSS software (version 20.0). Results: The participants were predominantly male and above the age of 60, and this age group was significantly associated with a higher risk of death. Symptoms such as fever (OR=3.81) and absence of cough (OR=2.31), as well as the use of sedatives (OR=4.47) and vasoactive drugs (OR=20.14), were found to be significantly associated with an increased risk of mortality. When comparing the biomarkers of patients hospitalized in the ICU who were discharged versus those who died, higher mean values were observed for prothrombin time, activated partial thromboplastin time, D-dimer, urea, creatinine, potassium, leukocytes, PCR, and glucose levels among the deceased patients. Conversely, lower mean levels of albumin were observed in those who did not survive. Implications: Therefore, these biomarkers can contribute to the assessment of disease progression and monitoring the health status of patients treated in ICU settings.